Manajemen Pendidikan Islam Dalam Implementasi Kurikulum di Taman Kanak-Kanak - Rumiyanti; Fadlilah; Yusria (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to comprehensively examine the management of early childhood education curriculum implementation at TK PKK Muaro Jambi, with a focus on the integration of Islamic values in three main aspects: planning, implementation, and evaluation. The research employed a qualitative approach using field study methods and data collection techniques such as observation, interviews, and documentation. The findings revealed that planning was carried out through structured learning modules, although it has not fully addressed individual student needs. The implementation included Islamic values through daily routines, but the teaching methods remained less responsive to children's diversity. Evaluation used authentic assessment tools but has yet to be optimized as a basis for improving teaching practices. The study concludes that while the management of learning at TK PKK Muaro Jambi is relatively effective, it requires further improvement through more adaptive, inclusive approaches grounded in Islamic educational values.